2007
DOI: 10.2353/ajpath.2007.060699
|View full text |Cite
|
Sign up to set email alerts
|

Leptin-Dependent Toll-Like Receptor Expression and Responsiveness in Preadipocytes and Adipocytes

Abstract: Leptin, an adipokine mainly produced by adipocytes, has been well characterized with regard to its regulatory function on immune cells. Thus the question occurred of how adipocytes and preadipocytes interact with the immune system and whether or not this communication is regulated by leptin. With the present study we evaluated the Toll-like receptor (TLR) expression and TLR ligand-specific activation of murine preadipocytes and adipocytes in the presence [wild type (WT), 3T3L1] or absence of leptin (ob/ob) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 57 publications
2
81
0
5
Order By: Relevance
“…Recent data indicate an additional function for this cell population since they are not only capable of phagocytosis but, furthermore, have been shown to express functional TLR (5). With the present study, the expression and function of the nucleotide-binding site and leucine-rich repeat protein nucleotide oligomerization domains 1 and 2, belonging to the recently discovered family of pattern recognition receptor family localized in the cytoplasm, were characterized in preadipocytes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recent data indicate an additional function for this cell population since they are not only capable of phagocytosis but, furthermore, have been shown to express functional TLR (5). With the present study, the expression and function of the nucleotide-binding site and leucine-rich repeat protein nucleotide oligomerization domains 1 and 2, belonging to the recently discovered family of pattern recognition receptor family localized in the cytoplasm, were characterized in preadipocytes.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, preadipocytes have the potential to differentiate into the macrophage lineage and have been shown to phagocytose (4). Our group demonstrated that adipocytes and preadipocytes express functional TLR in a leptin-dependent manner (5) suggesting that these cells might belong to the innate immune system.…”
mentioning
confidence: 79%
“…Moreover, several studies have described interplays between TLR signaling and adipokines. In a recent report, significant upregulation of TLR1 to −9 expression in preadipocytes and adipocytes of ob/ob and db/db mice was demonstrated, revealing a strong regulation of TLR expression by leptin (Batra et al, 2007). In a different study, adiponectin has been shown to negatively regulate macrophage-like cell response to TLR ligands (Yamaguchi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These polymorphisms have been associated with IL6 promoter activity, plasma levels of IL6 [30,31] or ACE [25] and responsiveness of the AT1R [32]. There are several lines of experimental evidences which also support a potential link between TTV infection and inflammation or body weight: 1. transfection of TTV ORF2 into human cell lines could suppress NF-kB activity and transcription of different NF-kB-mediated downstream genes, including IL6 [33]; 2. mice preadipocytes and adipocytes can express Toll-like receptors 9 which can modify IL6 production in response to specific stimuli [34]; TTV DNA can activate Toll-like receptors 9 and can stimulate production and secretion of IL6 by immune cells [35]; 3. some transgenic mice expressing TTV ORF1 [36] or high levels of circulating IL6 [37] present a reduced average body weight and low growth rate; primary infection with TTV can occur early in life [28] and abnormal body weight in early life was associated with risk for later diseases, including obesity [38]. The complex relationship between IL6, fat metabolism and obesity has been examined in many studies, yet the results are still conflicting.…”
Section: Discussionmentioning
confidence: 99%